Analisis Faktor-Faktor Yang Mempengaruhi Inflasi Di Pulau Sumatera Menggunakan Metode Regresi Data Panel - Tanjung, Kartika Anjalya; Sufri, Sufri; Kholijah, Gusmi (Journal of Mathematics, Computations and Statistics, 2022)
Inflation is a dilemma that haunts the economy of every country, especially for developing countries in the world. Inflation is an economic situation in which prices in general increase continuously over a long period of time. Some indicators that are considered to affect the occurrence of inflation, namely the consumer price index, gross regional domestic product, district/city minimum wage, and economic growth. One of the methods used in analyzing factors that affect inflation on the island of Sumatra is the Data Regression Panel Method which is an analysis to model the influence of free variables on bound variables over a certain period of time with an observation as an object in the study. This study conveys that the best regression model obtained is the Fixed Effect Model (FEM). The model conveys partially only variable consumer price index and economic growth that most significantly affect the rate of inflation on the island of Sumatra. However, all variables, namely the consumer price index, gross regional domestic product, district/city minimum wage, and economic growth in the FEM model together or simultaneously are able to explain the inflation rate on the island of Sumatra at 58.19%, the remaining 41.81% is explained by other variables outside the unexplored model.